The counterfeit heiress - Alexander, Tasha, 1969- (Alexander, Tasha, 1969- Lady Emily mystery., 2014)
"After an odd encounter at a grand masquerade ball, Lady Emily becomes embroiled in the murder investigation of one of the guests, a sometime actress trying to pass herself off as the mysterious heiress and world traveler Estella Lamar. Each small discovery, however, leads to more questions. Was the intended victim Miss Lamar or the imposter? And who would want either of them dead? As Emily and Colin try to make sense of all this, a larger puzzle begins to emerge: No one has actually seen Estella Lamar in years, since her only contact has been through letters and the occasional blurry news photograph. Is she even alive? Emily and Colin's investigation of this double mystery takes them from London to Paris, where, along with their friend Cécile, they must scour the darkest corners of the city in search of the truth"--